Designing force probes based on reversible 6π-electrocyclizations in polyenes using quantum chemical calculations - Bettens, Tom; Eeckhoudt, Jochen; Hoffmann, Marvin; Alonso, Mercedes; Geerlings, Paul; Dreuw, Andreas; De Proft, Frank (The journal of organic chemistry, 2021)
The conjugated π-system in polyenes can be interrupted by electrocyclic ring-closure reactions. In this work, this 6π-electrocylization is shown by means of density functional calculations to be reversible by the application of an external mechanical pulling force at the terminal ends of the interrupted polyene chain. The test systems were constrained in a fused ring system, thus locking the orientation of three π-bonds and generally promoting 6π-electrocyclic ring-closure reactions. For several systems, the forward reaction is exergonic and the corresponding reaction barrier is comparable to those reported in the literature. The reverse reaction is triggered by an external pulling force of 2 nN (nano-Newton) or less and also becomes exergonic in all investigated polyenes under these force conditions. Moreover, it proceeds via a low reaction barrier when a pulling force of 2 nN is active, indicating that the mechanical force is an efficient stimulus for triggering ring-opening reactions. Analysis of the strain energy induced by this mechanical force confirms an optimal activation of the corresponding C-C σ-bond that breaks upon ring opening when the pulling positions are located on the polyene chain.
Gesehen am 16.07.2021